5. Prospective pre-emptive EEG study prior to west syndrome. Issue 8 (August 2018) - Pinchefsky, Elana F; Wilson, Diane; Glass, Torin; Chau, Vann; Boulet, Jason; Nenadovic, Vera; Sharma, Roy; Wu, Ying; Melendres, Paula; Staley, Justine; Richards, Ann; Viljoen, Amrita; et al.
Abstract : Since the original description of hypsarrhythmia by visual inspection as a "chaotic" and disorganized pattern in 1954, we have continued this clinical practice of EEG interpretation with solely visual inspection until the present day. The description of hypsarrhythmia as "chaotic" [Gibbs EL, Fleming MM, Gibbs FA. Pediatrics 1954;13(1):66–73], was challenged by van Putten and Stam 17 years ago [IEEE Eng Med Biol Mag. 2001;20(5):72–9]. We are now conducting the first prospective study in newborn babies with risk factors for infantile spasms. Our rational is that 40 out of the 200 known risk factors can be detected during the neonatal period. After consent, we conduct the longitudinal EEG protocol every 2 months until 1 year of age. Phase synchrony and variability analyses are performed to detect the earliest EEG changes before hypsarrhythmia onset. The EEG analyses from the dynamics perspective opens a new examination of hypsarrhythmia and electrodecremental events (EDEs) in infantile spasms, beyond the sole visual inspection of the EEG. We will present cases to illustrate the value of the phase synchronization index and the temporal variability of the index. Preliminary data suggest that both abnormal EEG patterns, hypsarrhythmia and EDEs are associated with high phase synchronization. These preliminary findings question the prevailing notion that hysparrhythmia is a disorganized pattern and may account for the observed developmental stagnation in these children. The visual inspection of hypsarrhythmia does not appear sufficient to appreciate the highly synchronized EEG pattern in patients with infantile spasms.